Climate Change, South Asia and Southeast Asian Region (Global Journal of Science Frontier Research, 2021)
It is well known that the climatic conditions of our earth have changed since its origin. In its early days environmental conditions were not suitable for life. However, with due course of time it has changed and origin of life took place. Scientists have found seven cycles of glacial advance and retreat during the last 650,000 years and also that the last ice age abruptly ended about 7,000 years ago. The phenomenon of climate change has many implications and immense effects on our environment. There are many factors such as emissions of greenhouse gases, deforestation, urbanization and industrialization which impact the climate. Some of the major consequences of climate change include impacts on sea level rise in coastal areas, impacts on forestry, agriculture and food productivity, life and property in coastal areas, marine life, wildlife habitat and natural ecosystem, biodiversity, glaciers, floods and human health. This paper is an attempt to understand the phenomenon of climate change, historical evidences of climate change, identify reasons of global warming and climate change and its consequences in the South Asia and, in its neighbouring regions.
Keywords: climate change; global warming; impacts; south asia